Study Productivity of Glutamic Acid by Bacillus subtilis EN3 Isolated from the Soil - Al-Attar, Eman J.; Salih, Nidhal M.; Al-Rajhi, Shaymaa H. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The genus Bacillus bacterium isolated from soil and tests their ability to produce glutamic acid, the bacteria are diagnosed by traditional methods and VITEK-2 system. And we studied the optimal conditions for production and try to improve the productivity of the isolation by manipulating the components of the production medium and of the circumstances environmental of production medium. There is 43 isolates of the 70 bacterial isolates belonging to the genus Bacillus depending on phenotypic characteristics of the colonies and microscopic characteristics and found that 13 isolated revert to species B.subtilis depending on physiological and biochemical characteristics. As well as on microscopic and biochemical tests, 13 isolates were subjected to the diagnostic by VITEK-2 system. The results showed that EN5 and EN3 diagnosed as B.subtilis as well as a commercial isolate A1 was also diagnosed as B.subtilis was selected EN3 isolation, as highest productivity (2 mg/ml).then optimal conditions was studied to produce glutamic acid by using the semi synthesis medium contained waste of extract dates (DE) as best Carbone source at 10% and use of ammonium nitrate as the best source of nitrogen at 2% from the production medium, and achieved better productivity of glutamic acid amounted to 7.2 mg/ml, at the temperature 34Â°C, pH initial 6.5, ventilation and agitation increase concentration of glutamic acid product when the proportion of medium size to the size of the flask 5:1 in the shaker incubator speeds of 180 rpm, for incubated period of 72 hours, were obtained, improvement rate was amounted to 360% from what was produced wild isolation.